Інформаційна нерівність в сучасному суспільстві - Козлова, Олена Аркадіївна (ФОП Бровін О. В., 2015)
В тезах проаналізовані соціальні аспекти інформаційної нерівності в умовах формування інформаційного суспільства. Розглянуто і уточнено поняття інформаційної нерівності. Визначені соціальні чинники, які детермінують стан інформаційної нерівності в сучасному суспільстві, а також запропоновані заходи що до зниження рівня інформаційної нерівності.

The theses analyzes the social aspects of information inequality during the formation information society. Reviewed and refined the concept of information inequality. The article indicate the socially factors that determine the status of information inequality in a modern society and propose actions to reduce the level of information inequality.
Keywords: інформаційні технології; цифрова нерівність; комп'ютерні мережі; Інтернет; information society; information inequality; digital inequality; computer networks; Internet; information computer technology